Einstein : a hundred years of relativity - Robinson, Andrew (Princeton University Press, 2015)
With contributions from Freeman Dyson, Stephen Hawking, Joao Magueijo, Steven Weinberg, Philip Anderson, Robert Schulmann, Philip Glass, Max Jammer, Sir Joseph Rotblat, I. Bernard Cohen, and Sir Arthur C. Clarke. This definitive illustrated study of one of the foremost icons of the 20th century commemorates the centenary of Albert Einstein's annus mirabilis of 1905, the same year when Einstein, at age 26, published his groundbreaking Special Theory of Relativity, and when the most famous equation in science, E = mc2, was introduced to the world. --